Current laser therapy options for endoscopic treatment of upper tract urothelial carcinoma. (10th March 2023) - Zollinger, Benjamin W.; Shoen, Ezra J.; Gresham, Charles F.; Whalen, Michael J.
Abstract: Endoscopic management via retrograde ureteroscopic laser ablation of upper tract urothelial carcinoma (UTUC) has become the preferred treatment modality for low-risk tumors. The most popular ablative lasers over the past 15–20 years have been the holmium:yttrium-aluminum-garnet (Ho:YAG) and neodymium (Nd:YAG) lasers, but recently the thulium (Th:YAG) laser has emerged as a potential alternative. This review compares the mechanism of action, physiological properties and effects, and oncologic outcomes of Ho:YAG/Nd:YAG lasers versus the Th:YAG laser for UTUC treatment. Potential advantages of the Th:YAG laser over existing technologies are outlined, followed by a discussion of emerging laser technologies in UTUC management.